Ekstraksi Pektin dari Kulit Kakao (Theobroma cacao L.) Menggunakan Amonium Oksalat - Cut Erika (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
Cocoa (Theobroma cocoa L) is one of the local superior commodities in Aceh Province. The production of cocoa continues to increase significantly every year. Cocoa Pod husk is a waste product of cocoa beans industry, which is containing pectin with concentration ranged between 2-10%. Pectin extraction is one of the potential researches to increase economic value of cocoa pod husks. This study aimed to determine the effect of extraction time and pH on the characteristics of cocoa pod husk pectin. Pectin was extracted from cocoa pod husks using ammonium oxalate, extraction time (60 and 120 min) and pH (2.6, 3.6 and 4.6). The use of ammonium oxalate produced high yield of pectin ranged from 6.63 to 12.75%, moisture content was 7,36 to 10,77%, methoxyl content was 5.19 to 5.70%, anhydrogalacturonic acid of 59.84 to 63.14%, the esterification degree was 48.43 to 51.43 % and relative viscosity was 40 – 186,6 cP. The extraction time for 60 minutes at pH 3,6 showed a higher yield compared to 120 min at pH 4,6. Pectin on the extraction time of 60 minutes at pH 3.6 had the highest relative viscosity was 186,6 cP, and the lowest viscosity of pectin obtained at pH 2.6 and extraction time of 60 min which was 40 cP.Keywords: cocoa pod husks, ammonium oxalate, extraction time, pH